Performances of anaerobic and aerobic membrane bioreactors for the treatment of synthetic textile wastewater. (September 2015) - Yurtsever, Adem; Sahinkaya, Erkan; Aktaş, Özgür; Uçar, Deniz; Çınar, Özer; Wang, Zhiwei
Highlights: Anaerobic and aerobic MBRs were compared for dye containing wastewater treatment. Color was completely removed in the anaerobic MBR. AnMBR and AeMBR were successfully operated up to 9 LMH and 20 LMH, respectively. Higher filtration resistances were observed in AnMBR. Chemical cleaning almost completely removed fouling for both MBRs. Abstract: This study aims at comparatively evaluating anaerobic and aerobic MBRs for the treatment of azo-dye containing synthetic wastewater. Also, the filtration performances of AnMBR and AeMBR were compared under similar operating conditions. In both MBRs, high COD removal efficiencies were observed. Although almost complete color removal was observed in AnMBR, only partial (30–50%) color removal was achieved in AeMBR. AnMBR was successfully operated up to 9 L/(m 2 h) (LMH) and no chemical cleaning was required at 4.5 LMH for around 50 days. AeMBR was operated successfully up to 20 LMH. The filtration resistance of AnMBR was generally higher compared to AeMBR although reversible fouling rates were comparable. In both MBRs, offline chemical cleaning with NaOCl and sulfuric acid almost completely removed irreversible fouling and the resistances of chemically cleaned membranes were close to those of new membranes.